Change of Luminescence Properties of Europium Ions Captured by Mixed‐Ligand Silver Nanoparticles. Issue 5 (6th June 2014) - Cho, Eun Seon; Yokoyama, Takahiro; Ertem, Elif; Stellacci, Francesco
Abstract We present herein silver nanoparticles about 4 nm in diameter coated with a binary mixture of 1‐octanethiol and 2‐(2‐{2‐[(6‐mercaptohexyl)oxy]ethoxy}ethoxy)ethanol. These particles show an affinity towards optically active Eu3+ ions. The effect of the nanoparticle on the characteristic emission peaks of Eu3+ is investigated. We use the variation in emission spectra of the ion to establish its binding to the nanoparticles.